Cancer incidence and treatment utilization patterns at a regional cancer center in Tanzania from 2008-2016: Initial report of 2, 772 cases. (August 2020) - Olson, Adam C.; Afyusisye, Franco; Egger, Joe; Noyd, David; Likonda, Beda; Masalu, Nestory; Suneja, Gita; Chao, Nelson; Zullig, Leah L.; Schroeder, Kristin
Highlights: The Bugando Cancer Registry is the largest regional hospital-based cancer registry in Tanzania. The most commonly diagnosed cancers were cervical and breast cancer in females, and prostate and Kaposi sarcoma in males. Only 53.9 % of patients in the registry received a cancer treatment. Most cases (69 %) were determined based on histopathology diagnosis. Fewer than 12 % of expected cases based on population were recorded in the cancer registry, highlighting the need for expanded registry services. Abstract: Purpose: To describe cancer incidence and treatment utilization patterns at the regional cancer referral center for the Lake Zone of northwestern Tanzania from 2008 to 2016. Methods: This descriptive, retrospective study reviewed all cancer cases recorded in the Bugando Cancer Registry (BCR), a clinical and pathology based registry at the only cancer referral hospital in the region. Primary tumor site, method of diagnosis, HIV status, and cancer treatment were reported. Using census data, the 2012 GLOBOCAN estimates for Tanzania were scaled to the Lake Zone and adjusted for 2016 population growth. These estimates were then compared to BCR cases using one-sample tests of proportion. Results: A total of 2772 cases were reported from 2008−2016. Among these, the majority of cases (82.5 %, n = 2286) were diagnosed among adults. Most cases (85 %, n = 1923) were diagnosed by histology or cytology. Among adults, the most common cancers diagnosed were cervix (22.7 %, n=520), breast (12.6 %, n=288), and prostate (8.5 %, n=195). Among children, the most common cancers were non-Burkitt non-Hodgkin lymphoma (17.3 %, n=84), Burkitt lymphoma (16.5 %, n=80), and Wilms tumor (14.6 %, n=71). The 1116 BCR cases represent 12.2 % of the 9165 expected number of cancer cases for the Lake Zone (p < 0.001). 1494 cases (53.9 %) received some form of treatment - surgery, chemotherapy, radiation, or hormone therapy - while 1278 cases (46.1 %) had no treatment recorded. Conclusions: This comprehensive report of the BCR reveals cancer epidemiology and treatment utilization patterns typical of hospitals in low-resource settings. Despite being the only cancer center in the Lake Zone, BMC evaluates a small percentage of the expected number of cancer patients for the region. The BCR remains an important resource to guide clinical care and academic activities for the Lake Zone.